Effect of glycerol as an energy source with or without probiotic on carcass trait, litter moisture per cent, haematological and serum metabolites in broiler chicken - NAITAM, N D; MUNDE, V K; DESHPANDE, K Y; KEKAN, P M; SONALE, P D; GHOLVE, A U; NAITAM, S D (The Indian Journal of Animal Sciences, 2021)
An experiment was conducted to access glycerol feeding on the carcass traits, litter moisture %, haematological and serum metabolites of broiler chicken. The broiler chicks were randomly distributed in five groups, viz. T0 (0% glycerol), T1 (3% glycerol with probiotic), T2 (3% glycerol without probiotic), T3 (6% glycerol with probiotic) and T4 (6% glycerol without probiotic) with four replicates of 15 chicks, each of 45.8Â±0.23 g body weight. Results indicated that, the dressed breast weight and its percent was significantly higher in T1 followed by T2 and almost comparable in T3 and T4 as compared to control. LDL was significantly lower in T1 as compared to T0, T2, T3 and T4. The % litter moisture was significantly increased as glycerol inclusion level increased. From the results, it was concluded that 3% glycerol in diet with probiotic significantly improved dressed breast weight, lowered LDL and increased litter moisture with increase in glycerol level.